Structures of Cyclic Organosulfur Compounds From Garlic (Allium sativum L.) Leaves - Fukaya, Masashi; Nakamura, Seikou; Hayashida, Hitoshi; Noguchi, Daisuke; Nakashima, Souichi; Yoneda, Taichi; Matsuda, Hisashi (Frontiers in Chemistry, 2020)
Five new cyclic organosulfur compounds, foliogarlic disulfanes A1 (1), A2 (2), and A3 (3) and foliogarlic trisulfane A1 (4) and A2 (5), were isolated from the leaves of Allium sativum (garlic). The chemical structures of these compounds were elucidated on the basis of physicochemical evidence including Nuclear Magnetic Resonance (NMR) and Mass Spectrometry (MS). Compounds 1–5 were obtained as complex compounds with disulfane or trisulfane and tetrahydro-2H-difuro[3,2-b:2′,3′-c]furan-5(5aH)-one. In addition, the hypothetical biosynthetic pathways of these compounds were suggested.